2006
DOI: 10.1387/ijdb.052110cm
|View full text |Cite
|
Sign up to set email alerts
|

The zic1 gene is an activator of Wnt signaling

Abstract: The zic1 gene plays an important role in early patterning of the Xenopus neurectoderm. While Zic1 does not act as a neural inducer, it synergizes with the neural inducing factor Noggin to activate expression of posterior neural genes, including the midbrain/hindbrain boundary marker engrailed-2. Since the Drosophila homologue of zic1, odd-paired (opa), regulates expression of the wingless and engrailed genes and since Wnt proteins posteriorize neural tissue in Xenopus, we asked whether Xenopus Zic1 acted throu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
64
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 52 publications
(68 citation statements)
references
References 56 publications
3
64
1
Order By: Relevance
“…Another study determined that the C-terminus of Zic2 contains both activation and repression domains (Brown et al, 2005). Furthermore, Zic proteins devoid of the regions N-terminal to the zinc finger domain tend to act as dominant interfering proteins in Xenopus embryos (Kitaguchi et al, 2000;Nakata et al, 2000;Houston and Wylie, 2005;Fujimi et al, 2006;Merzdorf and Sive, 2006), suggesting that the N-termini may mediate positive regulatory activities. The N-and C-terminal domains of Zic proteins represent potential cofactor binding sites that are likely to modulate Zic activities, either to enhance or inhibit transcriptional activation or repression.…”
Section: Direct Targets Of Zic Proteinsmentioning
confidence: 99%
See 3 more Smart Citations
“…Another study determined that the C-terminus of Zic2 contains both activation and repression domains (Brown et al, 2005). Furthermore, Zic proteins devoid of the regions N-terminal to the zinc finger domain tend to act as dominant interfering proteins in Xenopus embryos (Kitaguchi et al, 2000;Nakata et al, 2000;Houston and Wylie, 2005;Fujimi et al, 2006;Merzdorf and Sive, 2006), suggesting that the N-termini may mediate positive regulatory activities. The N-and C-terminal domains of Zic proteins represent potential cofactor binding sites that are likely to modulate Zic activities, either to enhance or inhibit transcriptional activation or repression.…”
Section: Direct Targets Of Zic Proteinsmentioning
confidence: 99%
“…One such gene that is induced by all Xenopus zic genes is the midbrain/hindbrain boundary marker en-2 (Nakata et al, 1997(Nakata et al, , 1998Kuo et al, 1998;Fujimi et al, 2006). Additional genes induced by expression of zic1 include the dorsal neural tube marker pax3 (midbrain, hindbrain, spinal cord; Bang et al, 1997) and various dorsally expressed wnt genes, including wnt1 (midbrain/hindbrain boundary, hindbrain; Wolda et al, 1993), wnt4 (forebrain/midbrain boundary, midbrain; McGrew et al, 1992), and wnt8b (forebrain/midbrain boundary, midbrain; Cui et al, 1995) (Kuo et al, 1998;Merzdorf and Sive, 2006). zic1 also activates the hindbrain genes krox20, hoxD1, and Xfeb (Kuo et al, 1998;Li et al, 2006).…”
Section: Xenopus Neural Tube Developmentmentioning
confidence: 99%
See 2 more Smart Citations
“…ZIC1, the target of miR-101, has been suggested to be an upstream regulator of several Wnt pathway genes including WNT1, WNT4, and WNT8B, 32 and its expression has been described in fibroproliferative diseases including Dupuytren's contracture. 33 Furthermore, Degreef et al 34 reported on coexpression of ZIC1 and b-catenin in Dupuytren's contracture samples.…”
mentioning
confidence: 99%